Analisis Bibliometrik: Gaya Kepemimpinan dalam Penguatan Budaya Sekolah di Sekolah Islam - Robby Haryanto; Rugaiyah; Kamaludin (JIMAD: Jurnal Ilmiah Mutiara Pendidikan, 2026)
Research on leadership styles and the strengthening of school culture in Islamic schools has become increasingly significant in response to the growing demand for educational quality grounded in religious values. School principals play a strategic role in developing an adaptive, collaborative, and character-oriented organizational culture that supports students’ holistic development. This study focuses on publication trends, thematic cluster structures, and the tendencies of leadership style implementation in strengthening Islamic school culture based on bibliometric analysis. The study employed a descriptive quantitative approach using bibliometric analysis of 397 Scopus-indexed documents published between 2019-2025. Data collection was conducted using Publish or Perish, while data visualization analysis was performed using VOSviewer through keyword co-occurrence techniques. The findings reveal that school culture and distributed leadership emerged as the most dominant themes and occupied central positions within the bibliometric network. The shift in research paradigms indicates a transition from structural approaches toward participatory, collaborative, and contextual approaches in modern educational leadership. Another finding demonstrates that the concepts of Islamic school and Islamic leadership have not yet appeared prominently in international research networks, thereby indicating a significant research gap regarding the integration of Islamic values into school culture and educational leadership practices. This study concludes that the strengthening of school culture is influenced not only by the administrative capabilities of school principals, but also by their ability to foster collaboration, social relations, innovation, and the continuous internalization of moral values. The novelty of this research lies in the use of bibliometric analysis to systematically map the relationship between leadership styles and Islamic school culture, while also offering a perspective on integrating the values of amanah, shura, and exemplary conduct into modern collaborative leadership models.